Estudo da produção e caracterização de metacaulinita para utilização como material cimentício - (:unkn) unknown (Universidade Federal do Amazonas, 2019)
In the northeast of Amazonas, the kaolin belonging to the Alter do Chão formation emerges along the access roads to the municipalities of Manaus, Presidente Figueiredo and Itacoatiara, such as BR-174 and AM-010. This material when subjected to thermal activation by calcination, under certain temperature ranges, results in an amorphous material with disordered crystalline structure, called metakaolin or metakaolinite (MK). It has good reactivity with calcium hydroxide present in mixtures made of Portland cement, which makes it suitable for use as supplementary cementitious material in the production of pastes, mortars and concretes. Thus, the present research has the general objective to characterize the kaolin collected from BR 174 for the production of metakaolin and its use as supplementary cementitious material in cementitious pastes. The possibility of use in cementitious pastes implies its chemical and microstructural characterization through the techniques of X-ray fluorescence, X-ray diffraction (XRD), thermogravimetric analysis (TG / DTG / DTA), infrared spectroscopy (FTIR) and scanning electron microscopy (SEM). The transformations occurred in this material resulting from the calcination treatment to which it was submitted were studied, this occurred in the temperature ranges of 600 ºC, 650 ºC and 700 ºC in the time intervals of 1h, 2h and 3h in a muffle furnace. The analyzes carried out established the calcination at a temperature of 650 ºC with a time of 1h. In the chemical composition, there was a predominance of silicon oxide (SiO2) and aluminum oxide (Al2O3), compatible with the composition of the main mineral identified in the DRX, kaolinite. To evaluate the behavior of metakaolin produced as supplementary cementitious material, it was used to partially replace cement in cementitious pastes in the contents of 20% to 60%. These pastes were characterized by the techniques of CKD, TG / DTG, SEM and resistance to compression at the ages of 7, 28 and 91 days of cure.
Keywords: Caulinita; Cimento; Metacaulinita; Pastas cimentícias; Calcinação (Metalurgia); ENGENHARIAS: ENGENHARIA CIVIL: CONSTRUÇÃO CIVIL: MATERIAIS E COMPONENTES DE CONSTRUÇÃO; Caulim amazônico; Caulinita; Metacaulinita; Material cimentício suplementar